MANAJEMEN BUDAYA LITERASI MELALUI KEGIATAN APEL PAGI DI MADRASAH ALIYAH NEGERI 3 MANDAILING NATAL - Auliya Nasution, Mursyidan; Sulthan Arrasyid Nasution; Ananda Fahmul Afkar; Ahmad Riadi; Sunanto Nauli; Muharnita Azizah Rangkuti; Tauhid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low national literacy index necessitates innovative managerial re-engineering at the educational unit level to foster a competitive learning ecosystem. This study aims to analyze the management of literacy culture through the